A Ricardian analysis of the impact of climate change on Italian agriculture. (17th November 2017) - Bozzola, Martina; Massetti, Emanuele; Mendelsohn, Robert; Capitanio, Fabian
Abstract: This research investigates the potential impact of warming on Italian agriculture. Using a detailed dataset of 16, 000 farms across Italy, the study examines likely warming impacts in different regions and for different sectors of Italian agriculture. The study finds that farm net revenues are very sensitive to seasonal changes in temperature and precipitation. Livestock and crop farms have different responses to climate as do rainfed farms and irrigated crop farms. The overall results suggest mild consequences from marginal changes in climate but increasingly harmful effects from more severe climate scenarios.